Epigenetics and Expression of the Wnt Signaling Pathway in Ulcerative Colitis - Altintas, Zuhal; Erdal, Mehmet Emin; Altintas, Engin (Turkish Journal of Gastroenterology, 2025)
Background/Aims: Secreted frizzled-related proteins (SFRPs) are antagonists that bind Wnt and inhibit signaling through this pathway. Secreted frizzled-related proteins are silenced by promoter methylation and cause hyperactivation of the Wnt pathway. In this study, the aim was to evaluate the relationship between methylation and expression of genes involved in the Wnt signaling pathway and the risk of cancer development in inflammatory bowel disease. Materials and Methods: The patient group consisted of 20 individuals who were diagnosed with left-side ulcerative colitis and under went surveillance colonoscopy; the control group consisted of 15 individuals without symptoms and endoscopic pathology who were screened for colorectal cancer. Tissue samples were obtained from inflamed and non-inflamed areas of the colon. Methylation and gene expression profiles of the Wnt pathway genes APC1A, APC2, SFRP1, SFRP2, SFRP4, and SFRP5 were analyzed from DNA and RNA obtained from these tissues. Results: A significant correlation was found between the methylation status and expression of the SFRP4 gene in the proximal colon in the patient group compared to controls (P = .018). For the methylation of the APC2 gene, 8 patients were methylated (40%), and 12 were unmethylated (60%), while 1 of the controls was methylated (6.7%) and 14 were unmethylated (93.3%) (P = .018). There was no statisti cally significant association between methylation, expression, and inflammation status for other genes between patients and controls. Conclusion: In ulcerative colitis, inflammation is thought to be associated with both increased APC2 methylation and decreased expres sion findings due to decreased SFRP4 methylation in non-inflamed areas. However, more research is needed to establish a link with ulcerative colitis-related neoplasia. Cite this article as: Altintas Z, Erdal ME, Altintas E. Epigenetics and expression of the Wnt signaling pathway in ulcerative colitis. Turk J Gastroenterol. 2025;36(8):508-514.